UJI EFEK HIPOGLIKEMIK EKSTRAK ETANOL BUAH SAWO MANILA (Manilkara zapota) PADA MENCIT JANTAN YANG DIINDUKSI ALOKSAN - Aulia Wati; Safriani Rahman (Fakultas Farmasi UMI, 2016)
Diabetes mellitus is a metabolic disorder of carbohydrate, fat and protein that is characterized of hyperglycemia. Manila sapodilla (Manilkara zapota) empirically has been used by people as a traditional medicine. This study aims to determine the hypoglycemic effects and an effective concentration of ethanol extract manila sapodilla fruit as hypoglycemic on male mice induced by alloxan. The group of test animals consisted of 25 mice balb / c males were divided into 5 groups. Negative control group Na.CMC suspension 1% w / v, the comparison group glibenclamide 0.65 mg/kgbw, and group 3, 4, and 5 are a group of ethanol extract manila sapodilla fruit (EBSM) at a doses of 250 mg/kgbw, 500 mg/kgbw, and 750 mg/kgbw. Before treatment all test animals alloxan induced a dose of 150 mg/kgbw intraperitoneally (i.p). Given the test preparation is done orally once daily for 21 days. Blood collection from tail vein of mice on day 1 (h- 3rd), -3, -7, -11, -14, -17 and days 21 during treatment. Measurement of blood glucose levels is done before induction as early glucose levels, glucose levels after induction as diabetes mellitus, and after the end of therapy as glucose levels. The results were analyzed statistically by t-test and one-way ANOVA. Results showed EBSM a dose of 250 mg/kgbw showed no significant different compared to glibenclamide suspension. From this study it can be concluded that manila sapodilla fruit extract has hypoglycemic effects with an effective dose of 250 mg/kgbw. Keywords : Hyperglycemia, Manilkara zapota, male mice, alloxan.